Sports injuries and illnesses during the Winter Olympic Games 2010 - Engebretsen, L.; Steffen, K.; Alonso, J. M.; Aubry, M.; Dvorak, J.; Junge, A.; Meeuwisse, W.; Mountjoy, M.; Renström, P.; Wilkinson, M. (British Journal of Sports Medicine, 2010)
Background: Identification of high-risk sports, including their most common and severe injuries and illnesses, will facilitate the identification of sports and athletes at risk at an early stage.